Moral feelings scale - construction and psychometric properties - Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2010)
The paper reports construction process, validation and psychometrie properties of the Morał Feelings Scalę (SUM) new instrument of measuring different morał emotions. It was assumed that the two main classes of situations in which people experience morał emotions are situations where a violation and fulfillment of morał norms takes place. In respect to this, the SUM is comprised of two parts: A and B. Examination using SUM consists of freąuency assessment of given feelings experience in situations of transgressing morał norms (Part A) and their observance (Part B). The SUM contains the following subscales: Immature feelings (positive and extemalizing emotions), Fear of punishment, Shame, Global guilt, Sense of contrition (specific guilt) in the Part A, and Negative feelings, Hope for a reward, Sense of self-worth, Duty in relation to principles in the Part B. The article presents three studies samples included 196, 201 and 180 students. Apart from SUM other measures of guilt, shame and related variables were used (e.g. Test ofSelf Conscious Affect, Tangney, Dearing, 2002). Results of these researches seem to justify conclusion that SUM is a promising instrument with satisfactory psychometrie properties (Struś, 2009).